A transcultural comic series caught between nationalism and globalisation. Issue 3 (4th May 2019) - Gamache, Geneviève
ABSTRACT: Grant Morrison's 18 Days, the Mahabharata is a graphic series adaptation of an Indian epic poem of monumental proportions with deeply religious and philosophical content. Yet the goal behind the series was not to create a regional, or even national product, but to create a series that would be understandable to a global audience. Instead of being a product of glocalisation, the comic series is an example of the Local going Global. As the authors behind the series explain, although the Mahabharata is one of the most interesting and complex stories in the world, it is generally unknown to Western audiences. To bring this unfamiliar story to a global audience, the writers had to create a familiar visual environment for the readers to recognise. The comic divested itself of traditional, cultural and geographical signifiers, which are important elements of Indian popular culture. By doing so, it created a non-essentialist representation available to a larger, global audience. Yet it created this familiar environment using problematic representations of differences.